INTRODUCTION TO STEM CELLS - Khekare, Preetesh C.; Sonaye, Harsha V.; Doifode, Dr. C. A.; Bire, Priyanka A. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Stem cells are unspecialized cell. They are capable of continuous self-renewal. They can giverise to specialized cell types. Since the discovery of stem cells till now the totipotency is shownby very early embryonic stem cells. The adult stem cells possess multipotency and differentialplasticity which can be exploited for future generation of therapeutic options. Mechanisms ofstem cell maintenance are key to the regulation of homeostatis and likely contribute to aging.Stem cell therapy is useful in some of the disease. All said and done, stem cell research is still inthe form of research and it’s therapy form would take few decades more